(untitled) (Canadian Medical Education Journal, 2021)
Background: The use of rural rotations within urban-based postgraduate programs is the predominant response of medical education to the health needs of underserved rural populations. The broader impact on rural physicians who teach has not been reported. Methods: This study examined the personal, professional, and financial impact of a rural rotations for urban-based family medicine (UBFM) residents on Canadian rural teaching physicians. A survey was created and reviewed by community and academic rural physicians and a cohort of Canadian rural family physicians teaching UBFM residents was sampled. Survey data and free-text responses were assessed using quantitative and qualitative analyses. Results: Participants with rural residency backgrounds perceived a negative impact of teaching UBFM (p = 0.02 personal and professional) and those in a primary rural environment (as defined below) perceived impact as positive (p < 0.001). Rural preceptors often held contrasting attitudes towards learners with negative judgements counter-balanced by positive thoughts. Duration in practice and of teaching experience did not have a significant impact on ratings. Conclusion: Being a rural preceptor of UBFM residents is rewarding but also stressful. The preceptor location of training and scope of practice appears to influence the impact of UBFM residents.